Escalation of High School Students' Shot-Put Learning Outcomes Through Play Methods - Kamadi, La; Awaluddin; Ridwan, Andi; Bachtiar, Ishak; Fatoni (ETDC: Indonesian Journal of Research and Educational Review, 2024)
The goal of this study is to determine whether the playing method approach improves shot put learning outcomes for high school students. The research subjects were 36 students in class X Science 2 of Senior High School, Makassar. This study conducted classroom action research in two cycles, with each cycle encompassing planning, action, observation, and reflection. Tests, documentation, and observation are used to collect data. The research results showed that in the first cycle analysis, there were 15 students (42%) in the complete category, and in the second cycle, there was a significant increase, with 35 students (97.2%) in the complete category. According to my observations, 42% of student learning outcomes in cycle I increased by 97.2% in cycle II. According to observations from cycles I and II, applying the playing method can improve learning outcomes in shot put.